Nigeria Agriculture and Rural Poverty : A Policy Note - World Bank (Washington, DC, 2014)
The Nigerian labor force, like that of many countries in Africa, is heavily concentrated in agriculture. According to World Bank reports, the agricultural sector in Nigeria grew by about 6.8 percent annually from 2005-2009. This report focuses on the characteristics of the agricultural sector and rural households in Nigeria, and their implications for poverty. This report examines the relationships using nationally representative data from the general household survey panel (GHS), 2010-11. It was found that an elasticity of poverty reduction with respect to agricultural productivity of between 0.25 to 0.3 percent implying that a 10 percent increase in agricultural productivity will decrease the likelihood of being poor by between 2.5 and 3 percent. Agriculture in Nigeria is varied across regions, and, not surprisingly, most households involved in the sector reside in rural areas. The report is organized as follows: section one gives introduction. Section two gives brief description of selected agricultural programs and the targets of government expenditure in the sector in recent decades. Section three presents detailed profile of rural households and the composition of economic activities with a particular focus on agriculture. Section four examines the determinants of agricultural productivity, and highlights the factors (land ownership, input use, labor, plot management, land tenure, and household characteristics) most important for small-holder productivity. Section five concludes.